Out-of-equilibrium lattice response to photo-induced charge-transfer in a MnFe Prussian blue analogue. Issue 21 (19th May 2021) - Azzolina, G.; Bertoni, R.; Mariette, C.; Cammarata, M.; Trzop, E.; Ecolivet, C.; Sander, M.; Levantino, M.; Tokoro, H.; Imoto, K.; Yoshikiyo, M.; Ohkoshi, S.; et al.
Abstract : Photo-induced charge-transfer in the RbMnFe Prussian blue analogue is coupled to a Jahn–Teller distortion, which results in an anisotropic crystalline lattice reorganization. Abstract : Photo-induced structural dynamics in molecular materials often involve two main components; local molecular distortions induced by the self-trapping of electronic excited state and incoherent lattice dynamics due to energy dissipation. The latter component frequently hinders clear manifestation at macroscopic scale of local self-trapped entities and their coupling to the lattice. The studied photoactive MnFe Prussian blue analogue exhibits no thermal expansion, which allows observing long-range lattice dynamics induced by the structural trapping of photo-induced charge-transfer (CT) states. The self-trapping of the photo-induced Mn III Fe II → Mn II Fe III is responsible for the emergence of various physical properties. At equilibrium, the lattice volume expansion and the ferroelastic Jahn–Teller distortion associated with the charge-transfer-based phase transition, evolve in a coupled way. Here, we use time resolved X-ray diffraction to investigate the anisotropic out-of-equilibrium lattice dynamics triggered by the self-trapping of photo-induced Mn III Fe II → Mn II Fe III CT. The observed dynamics evidence a decoupling of both types of lattice deformations in the time domain, with an impulsive lattice response driven by the local Jahn–Teller reorganization and a displacive volume expansion controlled by the long-lived photo-induced CT small-polarons, due to the population of antibonding orbitals centered on Mn–N bonds in the ( a, b ) lattice plane.